New geothermal fluid flow simulation modified after Gwell Wellbore model using IAPWS industrial formulation 1997 for the thermodynamic properties of water and steam and incorporating the effect of NACL salt on viscosity and surface tension - Remoroza, Alvin I. (2007)
A computer program for geothermal wellbore simulation was developed using Visual Basic.Net programming language. It is a modified version of GWELL, a text-based multi-feedzone simulator that can handle CO2-H2O system. It incorporates inputs for mass fractions of CO2 and NaCl that both affect the thermodynamic properties of water and steam. The simulator is a tool to predict fluid properties of the flowing fluids along the length of the well and approximate contributions in a multi-feedzone well.
The new geothermal wellbore simulator features plotting capabilities of simulated and measured well data, abilities to save and store input data for simulation, export simulation results to MS Excel and "*.dat" text file format, and save image files of the plot generated. It was validated using pressure and temperature flowing surveys of wells from Pataan Sector, Northern Negros Production Field. The simulator was able to accurately match both the temperature and pressure profiles of the wells studied. Correlations of Armand and Orkiszwenski were used to calculated phase velocities of vapor and liquid. Flow regime determination along the length of the well is based on correlation of Orkizwenski.
"May 2007."
Thesis (M.S. Chemical Engineering)--University of the Philippines, Diliman.
Keywords: Geothermal engineering -- Simulation methods -- Philippines -- Negros; Geothermal power plants -- Philippines -- Negros